Technical Standard of ＂Five-Tone Figurative Hypnosis＂ - ZHOU Xia; LI Li; SHEN Yan; LI Chengbin; LIU Zhimei; ZHANG Yikun; ZHANG Mingqian; YU Shaohong; WANG Hongxia; LU Yi; WANG Qin; REN Binbin; et al. (康复学报)
"Five-tone figurative hypnosis technique" is a mind-body therapy technique of traditional Chinese medicine based on the five-tone theory,combining the "figurative thinking" of traditional Chinese medicine and modern psychological hypnosis technique. Following the principle of "scientific,practical and normative" and combining theory and clinical practice, the formulation of "Operation specification of Five-tone figurative hypnosis technology" can provide reference and evidence-based basis for workers in related industries to implement "five-tone figurative hypnosis technology". This technical operation code is formulated from the aspects of technical scope, normative reference documents, terms and definitions,indications and contraindications, operation steps and requirements,operation process, treatment time and frequency, precautions and efficacy evaluation, forming a relatively standardized, scientific and unified operation guide. The terms and definitions mainly include five-tone therapy, figurative thinking, hypnosis, finger point, ideomotor response, suggestion and synesthetic effect. The indications mainly include non-organic sleep disorders, psychological and emotional disorders, and psychosomatic diseases. Contraindications mainly included schizophrenia and panic attack. The operation steps and requirements mainly include [music preparation (five-element music selection,audio and video selection, instrument selection and music intensity), environmental requirements, disinfection preparation, instrument preparation, patient preparation and practitioner preparation]; The operation process mainly includes first diagnosis interview, hypnotic introduction, concrete thinking establishment, hypnotic deepening, post-hypnotic suggestion and recall. This standard can provide correct operation guidance for Chinese medicine doctors, psychotherapists, psychological counselors,rehabilitation therapists, music therapists, health massage therapists,specialist nurses and other relevant practitioners to carry out this technology, and has good clinical applicability, safety and effectiveness.